Ethics Courses, Teaching Styles, Ethical Culture at Workplace and Values of Accounting Graduates in Malaysia - Dato' Hasnah Hj Haron; Nurul Nazlia Jamil; Nathasa Mazna Ramli; Fatin Arissa Parsimin; Zalailah Salleh (UKM Press, 2024)
Vol 20